Rapid loss of efficacy to the antiseizure drugs lamotrigine and carbamazepine: A novel experimental model of pharmacoresistant epilepsy. Issue 7 (10th June 2013) - Srivastava, Ajay K.; Alex, Anitha B.; Wilcox, Karen S.; White, H. Steve
Summary Purpose Kindling is a well‐established model of secondarily generalized partial seizures that is widely employed in the search for novel antiseizure drugs. During the kindling and postkindling acquisition phase, an active process of neuronal remodeling occurs. We tested the hypothesis that exposure to the voltage‐gated sodium channel blockers lamotrigine (LTG) and carbamazepine (CBZ) during the period of active remodeling will lead to a diminished therapeutic effect. Methods Two days after the last kindling stimulation, fully kindled rats were randomized to receive either 0.5% methyl cellulose (MC), LTG (30 mg/kg), or CBZ (40 mg/kg). The effect of LTG and CBZ on behavioral seizure severity and electrographic afterdischarge duration (ADD) was recorded. One week after this treatment, rats in both groups were rechallenged with LTG 30 or CBZ 40 mg/kg and their seizure score and ADD recorded. In vitro efficacy of LTG on neuronal action potentials was also evaluated using whole cell current clamp recording in hippocampal brain slices obtained from kindled control rats, LTG‐sensitive kindled rats, and LTG‐resistant kindled rats. Key Findings When acutely administered 48 h after the last kindling stimulation, LTG and CBZ blocked the expression of behavioral seizures and reduced the ADD. In contrast, a second challenge dose of LTG or CBZ administered after a 7‐day "no drug, no stimulation" period did not result in reduction of either the seizure score or the ADD. Interestingly, the potassium channel opener, ezogabine, also known as retigabine (EZG; 40 mg/kg), blocked the expression of behavioral seizures at both time points evaluated (i.e., 2 days and 9 days after last stimulation). In vivo resistance to LTG was associated with a similar reduction in the ability of LTG to limit action potential firing in CA1 neurons. LTG (50 μm) significantly decreased the number of action potentials generated by a depolarizing current pulse in neurons recorded from slices obtained from kindled control and LTG‐sensitive rats, but not in slices obtained from LTG‐resistant rats. Significance Collectively, results obtained from both in vivo and in vitro studies demonstrate that even a single exposure to the sodium channel blockers LTG, or CBZ, during the postkindling remodeling phase leads to an altered pharmacologic response to these two ASDs, but not to EZG. The LTG‐ and CBZ‐resistant amygdala kindled rats may serve as a useful model of therapy‐resistant epilepsy.